NIR Spectroscopy of Actaea racemosa L. rhizome – En Route to Fast and Low-Cost Quality Assessment - Bittner, Marian; Krähmer, Andrea; Schenk, Regina; Springer, Andreas; Gudi, Gennadi; Melzig, Matthias F. (Planta Medica, 2017)
Rhizomes of Actaea racemosa L. (formerly Cimicifuga racemosa) gained increasing interest as a plant-derived drug due to its hormone-like activity and the absence of estrogenic activity. According to the Current Good Manufacturing Practices guidelines and pharmacopeial standards, quality assessment of herbal starting materials includes tests on identity and substitution, as well as quantification of secondary metabolites, usually by HPTLC and LC methods. To reduce the laboratory effort, we investigated near-infrared spectroscopy for rapid species authentication and quantification of metabolites of interest.Near-infrared spectroscopy analysis is carried out directly on the milled raw plant material. Spectra were correlated with reference data of polyphenols and triterpene glycosides determined by LC/diode array detection and LC/evaporative light scattering detection, respectively. Quantification models were built and validated by cross-validation procedures. Clone plants, derived by vegetative propagation, and plants of a collection from different geographical origins cultivated in Berlin were analysed together with mixed batches from wild harvests purchased at wholesalers.Generally, good to excellent correlations were found for the overall content of polyphenols with coefficients of determination of R2 > 0.93. For individual polyphenols such as fukinolic acid, only models containing clone plants succeeded (R2 > 0.92). For the total content of triterpene glycosides, results were generally worse in comparison to polyphenols and were observed only for the mixed batches (R2 = 0.93).Next to quantitative analysis, near-infrared spectroscopy was proven as a rapid alternative to other, more laborious methods for species authentication. Near-infrared spectroscopy was able to distinguish different Actaea spp. such as the North American Actaea cordifolia and the Asian Actaea cimicifuga, Actaea dahurica, Actaea heracleifolia, and Actaea simplex.
Keywords: Actaea racemosa; Ranunculaceae; NIRS; quality control; polyphenols; triterpene glycosides